Investigation into the Effect of Photodynamic Therapy and Cisplatin on the Cervical Cancer Cell Line (A2780): Photodynamic Therapy and Cisplatin on A2780 - Zafari, Jaber; Zadehmodarres, Shahrzad; Javani Jouni, Fatemeh; Bagheri-Hosseinabadi, Zahra; Najjar, Nabaa; Asnaashari, Mohammad (Journal of Lasers in Medical Sciences, 2020)
Introduction: Cervical cancer is recognized as one of the major causes of mortality among elderly women. Although there are several different therapeutic worldwide guidelines, many researchers have focused on screening new methodologies and technologies to elevate the efficiency of cervical cancer treatment. The simultaneous use of photodynamic therapy (PDT) along with chemotherapy as cisplatin has achieved good aims in the treatment of cervical cancer. Methods: A2780 cells were treated with cisplatin, photodynamic progress (laser with methylene blue as a photosensitizer compound) and a combination of cisplatin and PDT. The lithic effect of the laser, methylene blue and their combination and the IC50 value of cisplatin were calculated for each group. The amount of malondialdehyde (MDA) as membrane lipid peroxidation product and released lactate dehydrogenase was measured in the medium. The toxicity of each agent was evaluated by the MTT technique. Results: The results show that a combination of PDT and chemotherapeutic agent cisplatin caused a twofold decrease in viable cervical cancer cells compared to each therapeutic progress. The combination of both laser therapy and cisplatin enhanced cancer cell membrane disruption by increased membrane lipid peroxidation and apoptotic enzyme activation by the elevation of lactate dehydrogenase activity. Conclusion: The results indicated that cisplatin combined with PDT had a greater therapeutic effect on A2780 as a cervical cancer cell line. Therefore, PDT in combination with chemotherapy enhances the effectiveness of chemotherapeutic agents by the disruption of the cancer cell membrane and switching the apoptosis progress with less adverse effects.